The Impact of Lemon Aromatherapy on Nausea and Vomiting Episodes Among First-Trimester Pregnant Women Experiencing Emesis Gravidarum at the Rum Balibunga Community Health Center - Susilarnawanty Folasimo; Tut Rayani Aksohini Wijayanti (Calory Journal Medical Laboratory Journal, 2025)
Nausea and vomiting are common symptoms experienced during early pregnancy, especially in the first trimester, and can adversely affect maternal comfort, nutritional intake, and overall well-being. In primary health care settings, these symptoms are often managed with pharmacological treatments; however, such approaches may raise concerns regarding safety, potential side effects, and accessibility for pregnant women. Therefore, there is increasing interest in non-pharmacological interventions that are safer and more practical. One alternative method is lemon aromatherapy (Citrus limon), which is believed to reduce nausea and vomiting by stimulating the olfactory system and promoting a relaxing effect. This study aimed to assess the effectiveness of lemon aromatherapy in decreasing the frequency of nausea and vomiting among first-trimester pregnant women diagnosed with emesis gravidarum at the Rum Balibunga Community Health Center. The research applied a pre-experimental design using a one-group pretest–posttest approach. A total of 30 pregnant women in their first trimester were selected through purposive sampling. The intervention involved inhalation of lemon aromatherapy over a specified duration. Data on the frequency of nausea and vomiting were collected before and after the intervention using a structured observation instrument. The data were analyzed using both descriptive and inferential statistics, with the Wilcoxon signed-rank test employed to determine differences between pre- and post-intervention results. The findings revealed a significant reduction in nausea and vomiting frequency after the intervention. Overall, lemon aromatherapy proved to be an effective, safe, and practical non-pharmacological option to support antenatal care services.